2009
DOI: 10.1021/cg8008078
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Morphology and Defect Luminescence in Precipitated ZnO Nanorod Powders

Abstract: ZnO nanorods were prepared at relatively low temperatures by homogeneous precipitation from zinc nitrate and urea in a water/ethylene glycol mixture. Crystal size and morphology are controlled by growth time and solvent composition. We observed a strong correlation between nanocrystals’ size/morphology and their optoelectronic defect-related properties. Smaller crystallites exhibited intense deep-defect luminescence and enhanced emission related to near-surface excitonic recombination. Longer growth times lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 37 publications
(69 reference statements)
4
31
0
Order By: Relevance
“…[1][2][3][4][5] Conventional uses of ZnO include varistors, piezoelectrics, sensors, photocatalysts, cosmetics and sunscreens. 6,7,8 Zinc oxide typically crystallises with the wurtzite hexagonal structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Conventional uses of ZnO include varistors, piezoelectrics, sensors, photocatalysts, cosmetics and sunscreens. 6,7,8 Zinc oxide typically crystallises with the wurtzite hexagonal structure.…”
Section: Introductionmentioning
confidence: 99%
“…At OH/Zn ratios of 11-12, single hexagonal rods 1-2 um in length were produced. The authors suggested growth occurred from solutions supersaturated with respect to Zn(OH) 4 2-. 25 The occurrence of a hexagonal prismatic morphology [26][27][28][29][30][31] is generally assumed to be a consequence of surface energy effects favouring the development of {10-10} and {0001} crystal faces.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the PL emission band centered in the UV region is caused by the radiative recombination of electron from conduction band with hole from the valence band. The broad PL emission band located in the visible region may be related to induced emission from some defects such as oxygen vacancies and zinc interstitials [29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the research activities on nanoscale ZnO synthesis and characterization have increased significantly in the last few years. Various synthetic approaches have been reported in the literature, including hydrothermal [17][18][19] and solvothermal methods [20][21][22], microemulsion [23], sol-gel method [24], and thermal decomposition of precursors [25,26]. These chemical processes are efficient methods for preparation of nanoparticles and may…”
Section: Introductionmentioning
confidence: 99%